Relação custo-benefício em redes ópticas hierárquicas - Rocha, Renato Silva (2011)
In this work we present a performance analysis of hierarchical optical networks based on two parameters: the blocking probability and financial cost. For the earliest, we have used a discrete event simulator, known as SEDRO. For the latest, two different models are presented in order to compare the trend of each one and evaluate the influence when variations of some parameters of the network occur. We also present the simulations results for the network analysis on various aspects, such as, the number of super nodes and wavelenghts. Therefore, we can analyze the two models, for networks of different sizes and configurations. We have also evaluated the network feasibility, network cost and the impact of some network parameters on its performance